Study of the impact of desertification on land use in the El Bayadh region, South-Western Algeria - Zaidi, Hachemi; Berrouaguia , Karim; Guerroudj, Amina; Tennah, Helima; Kachabia , El khansa; Hafidh, Zemour; Touzri, Kenza (Journal of Agriculture and Applied Biology, 2025)
Algeria's steppe rangelands, covering an extensive 32 million hectares, serve as a vital biological zone, functioning as a transitional buffer between the sub-humid northern areas and the parched Sahara to the south. These rangelands are crucial for preserving biodiversity and aiding local inhabitants, although they are progressively susceptible to desertification, a significant environmental peril in Algeria. The wilaya of El Bayadh, a significant steppe area, is notably impacted by this occurrence. This research examines land use alterations in the wilaya of El Bayadh from 1990 to 2022, using remote sensing methodologies and Geographic Information Systems (GIS) alongside Landsat TM satellite images. The aim is to observe the advancement of desertification and delineate the spread of sand deposits in three northern communes: Bougtoub, El Kaf Lahmar, and Tousmouline. The findings demonstrate a significant increase in silting over the research period, indicating substantial changes in land cover. These results emphasize the increasing severity of desertification and stress the need for prompt action to protect this delicate environment. This study offers significant geographical data and analysis, establishing a basis for formulating effective policies and methods to address desertification. Through the implementation of specific strategies, stakeholders and policymakers may alleviate the detrimental impacts of desertification, foster sustainable land use practices, and secure the enduring stability of Algeria's steppe areas. The research highlights the need of using modern geospatial technology to tackle environmental issues and enhance resilience in at-risk ecosystems.